Combined effects of elevated epilimnetic temperature and metalimnetic hypoxia on the predation rate of planktivorous fish. (9th October 2019) - Maszczyk, Piotr; Babkiewicz, Ewa; Ciszewski, Krzysztof; Dabrowski, Kamil; Dynak, Przemysław; Krajewski, Karol; Urban, Paulina; Żebrowski, Marcin; Wilczynski, Wojciech
Abstract: Increased temperature in the epilimnion and hypoxia in the metalimnion of a lake would result in an increase of positive-size-selective fish predation on zooplankton and in turn in a decrease of mean body size in zooplankton populations and communities. We tested this hypothesis in four types of experiments with juvenile rudd ( Scardinius erythrophthalmus ) foraging on Daphnia longispina in an indoor twin column tank system. In each experiment of the first three types, one column contained one of three types of experimental treatments differing from the control treatment (in the other column) by the following: (i) elevated temperature in the epilimnion, (ii) hypoxia in the metalimnion and (iii) simultaneous elevated temperature in the epilimnion and hypoxia in the metalimnion. In the fourth type of experiment, the gradients of temperature and oxygen concentration in both columns were the same, but prior to the experiments, Daphnia and fish in the control treatment were acclimated to normoxia and, in the experimental treatment, to hypoxia. The results confirmed our hypothesis, since the predation rate of fish was greater in each of the first three experimental treatments than in the control. We did not detect an effect of the acclimation to hypoxia on the predation rate of the fish.